Dysregulation of Npas4 and Inhba expression and an altered excitation-inhibition balance are associated with cognitive deficits in DBA/2 mice - Oberländer, Kristin; Witte, Victoria; Mallien, Anne Stephanie; Bengtson, C. Peter; Bading, Hilmar (Learning & memory, 2022)
Differences in the learning associated transcriptional profiles between mouse strains with distinct learning abilities could provide insight into the molecular basis of learning and memory. The inbred mouse strain DBA/2 shows deficits in hippocampus-dependent memory, yet the transcriptional responses to learning and the underlying mechanisms of the impairments are unknown. Comparing DBA/2J mice with the reference standard C57BL/6N mouse strain we verify an enhanced susceptibility to kainic acid induced seizures, confirm impairments in hippocampus-dependent spatial memory tasks and uncover additional behavioral abnormalities including deficits in hippocampus-independent learning. Surprisingly, we found no broad dysfunction of the DBA/2J strain in immediate early gene (IEG) activation but instead report brain region-specific and gene-specific alterations. The learning-associated IEGs Arc, c‐Fos, and Nr4a1 showed no DBA/2J deficits in basal or synaptic activity induced gene expression in hippocampal or cortical primary neuronal cultures or in the CA1, CA3, or retrosplenial cortex following spatial object recognition (SOR) training in vivo. However, the parietal cortex showed reduced and the dentate gyrus showed enhanced SOR-evoked induction of most IEGs. All DBA/2J hippocampal regions exhibited elevated basal expression of inhibin β A (Inhba) and a learning-associated superinduction of the transcription factor neuronal Per-Arnt-Sim domain protein 4 (Npas4) known to regulate the synaptic excitation-inhibition balance. In line with this, CA1 pyramidal neurons of DBA/2J mice showed fewer inhibitory and more excitatory miniature postsynaptic currents but no alteration in most other electrophysiological properties or gross dendritic morphology. The dysregulation of Npas4 and Inhba expression and synaptic connectivity may underlie the cognitive deficits and increased susceptibility to seizures of DBA/2J mice.